2018
DOI: 10.1161/str.49.suppl_1.78
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 78: Time to Endovascular Treatment and Outcomes in the DAWN Trial

Abstract: Introduction: It is well-established that, within 0-6 hours, the benefit of thrombectomy rapidly decays over time. The DAWN trial demonstrated that, in the presence of clinical-core mismatch (CCM), thrombectomy remains beneficial within 6-24 hours. We aim to assess the effect of time to randomization on outcomes in the DAWN. Methods: We used traditional multivariate logistic regression controlling age and NIHSS at baseline adding an interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 0 publications
2
44
1
Order By: Relevance
“…[ 13 ] While clinical benefit was shown out to 24 h, post hoc analysis has shown that a decay in efficacy is still seen with each hour of delay continuing to negatively affect functional independence. The absolute risk difference for mRS 0–2 at 8 h was 24.4% versus 35.5% at 24 h.[ 14 ] DEFUSE-3 enrolled 92 patients from 38 centers in the thrombectomy arm and 90 patients in the medical arm. For inclusion in the trial, the core size was required to be <70 cc and the ratio of ischemic tissue to infarct core 1.8 on perfusion imaging.…”
mentioning
confidence: 99%
“…[ 13 ] While clinical benefit was shown out to 24 h, post hoc analysis has shown that a decay in efficacy is still seen with each hour of delay continuing to negatively affect functional independence. The absolute risk difference for mRS 0–2 at 8 h was 24.4% versus 35.5% at 24 h.[ 14 ] DEFUSE-3 enrolled 92 patients from 38 centers in the thrombectomy arm and 90 patients in the medical arm. For inclusion in the trial, the core size was required to be <70 cc and the ratio of ischemic tissue to infarct core 1.8 on perfusion imaging.…”
mentioning
confidence: 99%
“…CT remains the mainstay in the imaging triage of suspected AIS-LVO patients for ET, though there have been limited improvements in the non-contrast assessment of core infarction. The increased accuracy of VIM core infarct delineation over NCCT is of particular clinical relevance given established core volume thresholds in determining ET candidacy [14,99,107,108]. While our findings also suggest that VIM more accurately estimated core infarction than CTP, commonly applied CBF<30% segmentation thresholds underestimate the core volume relative to a less restrictive CBF<38% threshold to reduce false exclusion of patients from ET [109].…”
Section: Discussionmentioning
confidence: 57%
“…CT perfusion has proven a valuable selection tool for endovascular therapy in recent years [99,108]. For CTP to be used as a selection tool it needs to be reliable and allow quantitative core-penumbra volume mismatch evaluation.…”
Section: Ct Perfusionmentioning
confidence: 99%
See 2 more Smart Citations